Information Needs and Information Seeking Behavior of Teachers of Special Education in Shillong, India - Laloo, Bikika; Buhril, Jocica L. (Journal of the American Academy of Special Education Professionals, 2013)
Teaching itself, though noble, is a challenging profession. Such a profession calls upon not only the intellectual capacities of the teacher, but the physical and emotional as well. In short, it is a unique profession. Teaching differently-abled students (special education), is even more challenging. By virtue of their teaching a special group of people, the special education teachers’ information needs and information seeking behavior are quite different from those of other teachers. This study tried to explore these unique needs of Special Education teachers in three Special Education schools in Shillong, Meghalaya and found that there do exist information needs and information seeking behaviors that distinguish Special Education teachers from other types of teachers, such as, for example, the need for information on the medical conditions of students and the teachers’ seeking information from medical professionals. Special education teachers in Shillong are not very different from those in other parts of the world with regard to their qualifications, work culture, teaching methods and information issues.